Sustaining knowledge through unity among people - Mhd. Sarif, Suhaimi (2020)
This study reports the lessons acquired from the first Friday Prayers Khutbah in 2020. The main topic is about seeking knowledge without an end. This topic reflects the sustainability of knowledge in bringing mercy and goodness to people and the world. This study uses participant observation approach in making sense on the context of Friday prayers and sermon. Indeed, very interesting beginning of year 2020 with the emphasis of knowledge.